The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4014/jmb.1405.05039
|View full text |Cite
|
Sign up to set email alerts
|

Genome of Betaproteobacterium Caenimonas sp. Strain SL110 Contains a Coenzyme F420 Biosynthesis Gene Cluster

Abstract: To probe the genomic properties of microbes thriving in desert lakes, we sequenced the full genome of a betaproteobacterial strain (SL110) belonging to the understudied genus Caenimonas of the family Comamonadaceae. This strain was isolated from a freshwater lake in the western Gobi Desert, Northern China. Its genome contains genes encoding carbon monoxide dehydrogenase, nitrate reductase, nitrite reductase, nitric oxide reductase, and sulfur oxidation enzymes, highlighting the potentially important contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…This notion is supported by the high diversity or specificity of particular pathways. Previous studies have discussed the distribution of F 420 biosynthesis genes in the genomes of microorganisms other than Archaea and Actinobacteria (Selengut and Haft, 2010; Li et al, 2014). In the present study, we showed a higher diversity of the F 420 biosynthesis gene cluster than previously assumed, suggesting a possible correlation between these genes and microbial adaptation to the brine pool.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is supported by the high diversity or specificity of particular pathways. Previous studies have discussed the distribution of F 420 biosynthesis genes in the genomes of microorganisms other than Archaea and Actinobacteria (Selengut and Haft, 2010; Li et al, 2014). In the present study, we showed a higher diversity of the F 420 biosynthesis gene cluster than previously assumed, suggesting a possible correlation between these genes and microbial adaptation to the brine pool.…”
Section: Discussionmentioning
confidence: 99%